TINGKAT KESULITAN KEUANGAN PERUSAHAAN DAN KONSERVATISME AKUNTANSI DI INDONESIA - . HENDRIANTO (Universitas Katolik Widya Mandala Surabaya, 2012)
The economic crisis is inevitable in the world economy. The economic crisis is one form of uncertainty in the business world. Although it can not be avoided, the economic crisis can be predicted in advance. So, when the company experienced financial distress during the economic crisis, not the cause of the economic crisis, but the incompetence of managers of those companies. To rise from financial distress, the company needs an injection of funds from investors. The problem is how to attract investors to want to invest in companies that are experiencing financial distress. To overcome this problem, conservative method applied to recording the company noted that financial statements. Due to accounting conservatism led the company has hidden reserves that can be used when experiencing financial hardship. From the results of the discussion can be concluded that (1) management uses of accounting conservatism in order to attract investors to invest even though the company is experiencing financial distress, (2) conservatism is used to reduce the excessive optimism of management and shareholders, (3) conservatism used to be restrict managers to take action to exaggerate earnings and manipulate financial statements.